L-Carnitine therapy in non-alcoholic steatohepatitis - Ahmet UYGUN; Abdurrahman KADAYIFÇI; Sait BAĞCI; Ahmet ERDİL and Salih DEVECİ and Mendane SAKA and Ateş YÜKSEL and Fatih BULUCU and Necmettin KARAEREN and Kemal DAĞALP (Turkish Journal of Gastroenterology, 2019)
-